2021
DOI: 10.3389/fmicb.2021.658113
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequence of Bacillus velezensis Strain GUMT319: A Potential Biocontrol Agent Against Tobacco Black Shank Disease

Abstract: Phytophthora nicotianae causes black shank, a serious soil-borne disease, in tobacco. In this study, the Bacillus strain GUMT319 was isolated from the rhizosphere of healthy tobacco plants grown in a field in Guizhou with a high incidence of tobacco black shank. Genome sequencing revealed that GUMT319 contained a single circular chromosome 3,940,023 bp in length, with 4,053 predicted genes and an average GC content of 46.6%. Based on phylogenomic analyses, GUMT319 was designated as Bacillus velezensis. The gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…In general, there is a lack of information regarding population dynamics to explain bacterial behavior in the plant host. In agreement with this conclusion, some reports have indicated that Bacillus biocontrol strains do not show high consistency in the field because they are not able to colonize successfully different plants and the colonization ability is dependent on the environmental conditions. , …”
Section: Isolation Sources and Colonization Abilitysupporting
confidence: 60%
See 2 more Smart Citations
“…In general, there is a lack of information regarding population dynamics to explain bacterial behavior in the plant host. In agreement with this conclusion, some reports have indicated that Bacillus biocontrol strains do not show high consistency in the field because they are not able to colonize successfully different plants and the colonization ability is dependent on the environmental conditions. , …”
Section: Isolation Sources and Colonization Abilitysupporting
confidence: 60%
“…In agreement with this conclusion, some reports have indicated that Bacillus biocontrol strains do not show high consistency in the field because they are not able to colonize successfully different plants and the colonization ability is dependent on the environmental conditions. 14,16 Regarding the advances in the elucidation of the factors involved in the colonization ability of B. amyloliquefaciens species, Fedele et al studied the colonization ability of commercial strains B. amyloliquefaciens QST713, D747, and FZB24 in grapes, observing the highest number of cells at 25 °C and 100% humidity. 48 Liu et al indicated that γpolyglutamic acid (γ-PGA) promoted the colonization ability of B. amyloliquefaciens C06 in stone fruits.…”
Section: Isolation Sources and Colonizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bacillus velezensis strain GUMT319 rhizobacteria was originally isolated from the rhizosphere of field-grown tobacco plants in Guizhou with a high incidence of tobacco black shank. Previous studies confirmed that GUMT319 is a useful biocontrol agent [28]. We treated the Vitis vinifera L. variety 'Sweet Sapphire' with GUMT319 by root irrigation to determine its impact on grape plant growth.…”
Section: Experimental Design and Plant Managementmentioning
confidence: 89%
“…Application of PGPR can help maintain sustainable agricultural development [ 8 , 24 , 25 , 26 , 27 ]. B. velezensis strain GUMT319 is a PGPR rhizobacteria isolated from Guizhou province [ 28 ]. In this study, we treated vineyard soils with GUMT319 to determine the effects of GUMT319 on grape yield and found that GUMT319 can function like a PGPR.…”
Section: Introductionmentioning
confidence: 99%